2022
DOI: 10.1111/jonm.13775
|View full text |Cite
|
Sign up to set email alerts
|

Medical–surgical nurse leaders' experiences with safety culture: An inductive qualitative descriptive study

Abstract: Aim The aim of this study is to describe safety culture as experienced by medical–surgical nurse leaders. Background Safety culture remains a barrier in safer patient care. Nurse leaders play an important role in creating and supporting a safety culture. Methods We used an inductive qualitative descriptive study using semistructured interviews, document review and observations in a Midwestern community hospital in the United States. Results Results of the study are as follows: making sure nurses are keeping pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…reported that the majority of nurses score high on the professional values scale in nursing subscales and reported that all items on the professional values scale in nursing nurses are essential concluding that education in nursing plays a vital role in acquiring and maintaining values The current study found a positive correlation between staff nurses' professional values, awareness of moral and moral issues, and respect (knowledge, self-assessment) among all head nurses at different testing times. Its conformity to Harton & Skemp (2022), a mix of workgroup supervisors' and coworkers' commitment to participating in the CREW method is a significant predictor of higher post-intervention ratings of work respect and a fair more important predictor of higher post-intervention perceptions of workplace respect improvements reported a significant positive relationship was found between professional nursing values and levels of self-esteem as a predictor for adherence work setting that free from moral and ethical problems so that its useful to nursing educators to focus their effort on promoting professional, competent, ethical behaviors, practices of nursing care with nursing professional values of future nurses, and also supported…”
Section: Discussionmentioning
confidence: 99%
“…reported that the majority of nurses score high on the professional values scale in nursing subscales and reported that all items on the professional values scale in nursing nurses are essential concluding that education in nursing plays a vital role in acquiring and maintaining values The current study found a positive correlation between staff nurses' professional values, awareness of moral and moral issues, and respect (knowledge, self-assessment) among all head nurses at different testing times. Its conformity to Harton & Skemp (2022), a mix of workgroup supervisors' and coworkers' commitment to participating in the CREW method is a significant predictor of higher post-intervention ratings of work respect and a fair more important predictor of higher post-intervention perceptions of workplace respect improvements reported a significant positive relationship was found between professional nursing values and levels of self-esteem as a predictor for adherence work setting that free from moral and ethical problems so that its useful to nursing educators to focus their effort on promoting professional, competent, ethical behaviors, practices of nursing care with nursing professional values of future nurses, and also supported…”
Section: Discussionmentioning
confidence: 99%
“…TQM, according to (3), improves performance by increasing quality, customer satisfaction, profitability, and productivity. However, even after implementing TQM practices, many organizations' performance, particularly public hospitals, remains uncertain (4). TQM systems implemented in healthcare organizations can improve patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…True economic effectiveness will be established through vastly improved cost management practices, and the healthcare industry will be moved from its current lowperformance level to a new standard of excellence. Furthermore, implementing TQM in health care, which is a patient-centered process, results in safe health services, patientcentered care, improved health outcomes, and patient satisfaction, provided the processes are well designed, implemented, and consistently executed (4). The TQM approach has demonstrated the potential for dramatic improvements in quality and cost in healthcare organizations, but it has also proven difficult to implement.…”
Section: Introductionmentioning
confidence: 99%